2016
DOI: 10.1590/1678-775720160185
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticle incorporation effect on mechanical and thermal properties of denture base acrylic resins

Abstract: Objective The aim of the present study was to evaluate the mechanical and thermal characteristics of two denture base acrylic resins containing silver nanoparticles (AgNPs).Material and Methods Two different acrylic denture base resins (heat-polymerized and microwave polymerized) containing 0.3, 0.8 and 1.6 wt% AgNPs were evaluated for flexural strength, elastic modulus and impact strength. The glass transition temperature (Tg) and relative heat capacity (Cp) of the samples were determined from the Differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 27 publications
0
49
0
11
Order By: Relevance
“…38 Recently, nanotechnological products have been incorporated into PMMA to induce antimicrobial properties; their effects on the mechanical properties have been evaluated. 39,40 For example, Köroğlu et al 39 studied the effect of silver nanoparticle (AgNP) addition on PMMA's mechanical and thermal characteristics, concluding that the incorporation of AgNPs, which are generally used for antimicrobial efficiency, affected the mechanical properties of the PMMA denture base depending on the concentration of nanoparticles. In contrast, Gad et al 40 reported that zirconia nanoparticles have an antifungal effect without affecting mechanical properties.…”
Section: Discussionmentioning
confidence: 99%
“…38 Recently, nanotechnological products have been incorporated into PMMA to induce antimicrobial properties; their effects on the mechanical properties have been evaluated. 39,40 For example, Köroğlu et al 39 studied the effect of silver nanoparticle (AgNP) addition on PMMA's mechanical and thermal characteristics, concluding that the incorporation of AgNPs, which are generally used for antimicrobial efficiency, affected the mechanical properties of the PMMA denture base depending on the concentration of nanoparticles. In contrast, Gad et al 40 reported that zirconia nanoparticles have an antifungal effect without affecting mechanical properties.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, high concentrations of nanoparticles produce agglomeration sites that adversely affect the material's properties. Moreover, it has been suggested that low concentartion of AgNP would reduce material costs and amount of monomer . Therefore, 0.05% AgNPs and 0.2% AgNPs were preferred in the present study.…”
Section: Resultsmentioning
confidence: 91%
“…However, when the AgNP dimensions are less than 3 nm, they are more cytotoxic than larger particles (25 nm) . AgNPs with a mean average size of 38 and 68 and less than 35 and 50 nm were used in previous studies . Therefore, 40, 50, and 60 nm AgNPs were preferred and the large AgNPs were not preferred in the current study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Köroğlu et al (2016) studied the effect of silver nanoparticles' (AgNPs) addition on PMMA's mechanical and thermal characteristics, concluding that the incorporation of AgNPs, which are generally used for antimicrobial efficiency, affected the mechanical properties of the PMMA denture base depending on the concentration of nanoparticles.…”
Section: Discussionmentioning
confidence: 99%